Information acquisition and learning from prices over the business cycle - Taneli Mäkinen; Björn Ohl (Bank of Finland, 2014)
We study firms' incentives to acquire costly information in booms and recessions to understand the role of endogenous information in explaining business cycles. We find that when the economy has been in a recession in the previous period, and firms enter the current period with a pessimistic belief, the incentive to acquire information is stronger than when the economy has been in a boom and firms share an optimistic belief. The cyclicality of the aggregate learning outcome is moderated by the price system, which transmits information from informed to uninformed firms, thus dampening information demand. Though learning from equilibrium prices acts to stabilize fluctuations by discouraging information acquisition, it can be welfare-enhancing to make information prohibitively costly to obtain.
URN:NBN:fi:bof-20140807381
Keywords: D51; D83; E32; 330